Evaluation of faculty members at Zarqa Private University for the quality of some of the procedures and programs used in the preparation of academics and teacher students - Shiab, Jafar Abdullah Mohammed (Journal of Educational and Psychological Sciences, 2018)
The study aimed at revealing the assessment of faculty members at Zarqa Private University for the quality of some of the procedures and programs used in the preparation of academics and students' teachers. To achieve the objectives of the study, the researcher used the analytical descriptive method. He constructed a tool for the study which consisted of (24) And a random sample of 274 members from Zarqa Private University was selected. The results indicate that the degree of teacher preparation and technological development in the light of the global standards for the use of technology on the tool as a whole obtained a general average of (3.51 of 5), rated (high). The order of the fields ranked in descending order according to the level of teacher preparation and technological development in the light of international standards for the use of technology: Standard processes and technology concepts, and received an average (3.55), standard planning and design learning environments, an average (3.52), productivity standard and professional practice, averaging (3.48). All of which are rated (high). The results showed that there were no statistically significant differences at the level of (α = 0.05) in the degree of teacher preparation and technological development in light of the international standards for the use of technology due to gender variable. In the light of the results, a number of recommendations and proposals were presented to increase the degree of integration of technology in the school administration in the schools of Amman governorate and the whole of the Kingdom of Jordan.
Keywords: assessment; academics; procedures and programs; preparing student teachers; Zarqa Private University